We will first clear y from the second equation.
![4x-14=y](https://img.qammunity.org/2023/formulas/mathematics/high-school/io52rfq3smy1krmjb6qtfjw93b65nr18v0.png)
which is equivalent to
![y=4x-14](https://img.qammunity.org/2023/formulas/mathematics/high-school/gpjg2hwywk8y7s4ugovkdodpv6f57aem17.png)
now, we change y by 4x-14 in the first equation and the solve for x.
![6x+3(4x-14)=12](https://img.qammunity.org/2023/formulas/mathematics/high-school/cl4ylrkaqw8rof3f3lydx76etrftnv7zov.png)
![6x+3(4x)-3(14)=12](https://img.qammunity.org/2023/formulas/mathematics/high-school/u01w5iytj41fw5evsn4pwi6vllmdqaa0ao.png)
![6x+12x=12+42](https://img.qammunity.org/2023/formulas/mathematics/high-school/62lrbdl0nmmifo7662qci88bsrrw4teu4i.png)
![x=(54)/(18)=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/up2tepgz9zybgzbq0woz0l1ypa9mbqpil6.png)
then x=3 and we replace it in the second equation to find the y value:
![4(3)-y=14\Rightarrow y=12-14=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/wvjqvu4ly31ks3r05xexp60i3pbryzb2lu.png)
then the solution to this system of equations is the ordered pair (3,-2)